2010
DOI: 10.1371/journal.pone.0010480
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Oligodendrocyte Differentiation from Human Embryonic Stem Cells

Abstract: BackgroundCells of the oligodendrocyte (OL) lineage play a vital role in the production and maintenance of myelin, a multilamellar membrane which allows for saltatory conduction along axons. These cells may provide immense therapeutic potential for lost sensory and motor function in demyelinating conditions, such as spinal cord injury, multiple sclerosis, and transverse myelitis. However, the molecular mechanisms controlling OL differentiation are largely unknown. MicroRNAs (miRNAs) are considered the “microma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 61 publications
0
126
2
Order By: Relevance
“…Although miR-205 has been reported as a potential regulator of CLDN11 in human embryonic stem cell differentiation, this miRNA did not appear to be involved in GSC differentiation into oligodendroglial lineage in our model (35). Another miRNA, miR-219, has been shown to be necessary and sufficient to promote oligodendrocyte differentiation (44).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although miR-205 has been reported as a potential regulator of CLDN11 in human embryonic stem cell differentiation, this miRNA did not appear to be involved in GSC differentiation into oligodendroglial lineage in our model (35). Another miRNA, miR-219, has been shown to be necessary and sufficient to promote oligodendrocyte differentiation (44).…”
Section: Discussionmentioning
confidence: 58%
“…1, A and B). We also analyzed the expression levels of miR-205 in GSCs, which has been reported as a potential regulator of CLDN11 in human embryonic stem cell differentiation (35), and found that miR-205 expression was at an extremely low level, and there was no evidence of dynamic alteration in response to serum in GSCs (supplemental Fig. 1C).…”
Section: Resultsmentioning
confidence: 98%
“…Focusing further on differentiation, we note that Letzen et al (2010) reported extensive miRNA profiles for eight stages of differentiation from human embryonic stem cells to terminally differentiated oligodendrocytes. Fortuitously, several miRNAs were assayed in both the Letzen work and in our work.…”
Section: Cell Culturementioning
confidence: 93%
“…Although it is not yet entirely clear whether the observed dysregulation of MRF in these models is a causal component of the demyelination or merely symptomatic of oligodendrocyte dysfunction and loss, our results support the notion that dysregulation of MRF in NPC1 or other diseases could feasibly have a key role in the ultimate loss of myelin. Although roles for MRF in human myelination have not yet been formally established, it is known that the human ortholog C11Orf9 is enriched in myelin-rich regions of the human brain (Oldham et al, 2008), downregulated in human fetuses with a lethal motor neuron/oligodendrocyte disease (Pakkasjarvi et al, 2005), and upregulated during differentiation of oligodendrocytes from human ES cells (Letzen et al, 2010), suggesting conserved roles in myelination between mice and humans. As such, identification of the mechanisms by which MRF expression is regulated and its roles in human diseases will be an important subject of future work.…”
Section: Mrf Ablation As a New Model For Studying Demyelinating Diseasementioning
confidence: 99%